Kajian Estetika Yang Beda Relief Candi Jawa Timur - R. Bambang Gatot Soebroto (Universitas Bandar Lampung (UBL), 2012)
Penelitian ini disusun untuk mendalami bidang estetika Arsitektur pada relief candi. Untuk mengkaji danmenguji estetika relief candi dipakai teori Komposisi Polykleitos dan Prasejarah (Dick Hartoko).Diambil sepuluh sampel dari masing-masing daerah (Jawa Tengah-Jawa Timur), lalu dibuatkan matrik, untuk mudah pembacaan. Menjelaskan kedua kasus dipakai metode kritik Deskriptif dari Wayne Attoe. Hasil penelitian menunjukkan, relief candi Jawa Tengah masuk kategori indah menurut teori barat Polykleitos, tidak indah menurut teori Prasejarah - Dick Hartoko dan sebaliknya.The research was designed to explore the field of aesthetic architecture in temple reliefs. To examine and test the theory of aesthetic composition of the reliefs used Polykleitos and Prehistory (Dick Hartoko). Ten samples taken from each region (Central Java, East Java), then made ?the matrix, for easy reading. Explain both cases the methods used descriptive criticism of Wayne Attoe. The results showed that the relief of the temple in Central Java is categorized according to the theory of western Polykleitos beautiful, not beautiful according to the theory of Prehistory - Dick Hartoko and vice versa.